The rate of force generation by the myocardium is not influenced by afterload - Fioretto, J.R.; Okoshi, M.P. [UNESP]; Okoshi, Katashi [UNESP]; Cicogna, A.C. [UNESP]; Bonatto, R.C.; Padovani, C.R. [UNESP]; Tucci, P.J.F. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 1997)
The influence of afterload on the rate of force generation by the myocardium was investigated using two types of preparations: the in situ dog heart (dP/dt) and isolated papillary muscle of rats (dT/dt). Thirteen anesthetized, mechanically ventilated and thoracotomized dogs were submitted to pharmacological autonomic blockade (3.0 mg/kg oxprenolol plus 0.5 mg/kg atropine). A reservoir connected to the left atrium permitted the control of left ventricular end-diastolic pressure (LVEDP). A mechanical constriction of the descending thoracic aorta allowed to increase the systolic pressure in two steps of 20 mmHg (conditions H1 and H2) above control values (condition C). After arterial pressure elevations (systolic pressure C: 119 ± 8.1; H1: 142 ± 7.9; H2 166 ± 7.7 mmHg; P<0.01), there were no significant differences in heart rate (C: 125 ± 13.9; H1: 125 ± 13.5; H2: 123 ± 14.1 bpm; P>0.05) or LVEDP (C: 6.2 ± 2.48; H1: 6.3 ± 2.43; H2: 6.1 ± 2.51 mmHg; P>0.05). The values of dP/dt did not change after each elevation of arterial pressure (C: 3,068 ± 1,057; H1: 3,112 ± 996; H2: 3,086 ± 980 mmHg/s; P>0.05). In isolated rat papillary muscle, an afterload corresponding to 50% and 75% of the maximal developed tension did not alter the values of the maximum rate of tension development (100%: 78 ± 13; 75%: 80 ± 13; 50%: 79 ± 11 g mm-2 s-1, P>0.05). The results show that the rise in afterload per se does not cause changes in dP/dt or dT/dt
Keywords: ventricular function; afterload; dP/dt; dT/dt; papillary muscle; isometric contractions